2001
DOI: 10.1128/mcb.21.18.6181-6188.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Nuclear Hormone Receptor-Interacting Protein RIP140 Regulates Binding of the Transcriptional Corepressor CtBP

Abstract: CtBP (carboxyl-terminal binding protein) participates in regulating cellular development and differentiation by associating with a diverse array of transcriptional repressors. Most of these interactions occur through a consensus CtBP-binding motif, PXDLS, in the repressor proteins. We previously showed that the CtBP-binding motif in E1A is flanked by a Lys residue and suggested that acetylation of this residue by the p300/CBPassociated factor P/CAF disrupts the CtBP interaction. In this study, we show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
130
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 40 publications
8
130
0
2
Order By: Relevance
“…CtBPs interact directly with several transcriptional coregulatory proteins, many of which share the PXDLS motifs described above (13,17,21). For example, a screen for CtBP cofactors identified CtBP interacting protein (CtIP) (22), which also binds BRCA1 and retinoblastoma gene product (Rb) tumor suppressor proteins (23,24).…”
mentioning
confidence: 99%
“…CtBPs interact directly with several transcriptional coregulatory proteins, many of which share the PXDLS motifs described above (13,17,21). For example, a screen for CtBP cofactors identified CtBP interacting protein (CtIP) (22), which also binds BRCA1 and retinoblastoma gene product (Rb) tumor suppressor proteins (23,24).…”
mentioning
confidence: 99%
“…3A). Interestingly, this PMDLSTXK motif is conserved in several bromodomain-containing proteins of the bromodomain and ET domain family, including Ring3, a chromatin-associated protein identified in a yeast twohybrid screen as a CtBP interacting protein (47,50). The finding that the CBP and p300 coactivators may contain a CtBPinteracting motif was interesting in light of previous data showing that the E1A, E6, and Twist proteins can inactivate the acetyltransferase activity of p300/CBP leading to transcriptional repression (51)(52)(53).…”
Section: Interaction Of Ctbp With Cbpmentioning
confidence: 76%
“…Indeed, the 5V-TG-3V-interacting factor protein has already been shown to interact with CtBP (46). In addition, the nuclear receptor -interacting repressors Tif1a and Rip140 also contain this motif (47). As CtBP has been described to interact with HDAC and HDAC complexes and to exhibit sensitivity to trichostatin A on certain promoters, it is Gal4AD-CtIP, Gal4AD-CtBP, or Gal4AD.…”
Section: Interaction Of Ctbp With Cbpmentioning
confidence: 99%
“…RIP140 has previously been shown to inhibit a number of ligand-activated nuclear receptors through direct receptor binding and recruitment of histone deacetylases and the transcriptional repressor, C-terminal-binding protein, to receptors in a ligand-dependent fashion (13,14,59). Fernandes and colleagues (60) showed that ligand-dependent corepressor (LCoR) has similar properties to RIP140 in repressing the activity of ligand-bound nuclear receptors (60).…”
Section: Discussionmentioning
confidence: 99%
“…The coregulator RIP140 contains 10 LXXLL motifs and like a classic coactivator interacts preferentially with ligand-bound nuclear receptors (11). However, RIP140 inhibits the transactivation function of ligand-bound nuclear receptors in reporter assays (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). RIP140 is now recognized as one of the first proteins of a unique class of coregulators that are able to repress ligand-bound nuclear receptors (23).…”
mentioning
confidence: 99%